Faces of agreement between the interpretation of Al-Tibyan and those who preceded it from the Shiite commentators in the curriculum, the sources) are a comparative study - قاسم بستاني / مينا شمخی / عماد كاظم مانع ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The research on the aspects of agreement among the commentators is of great importance in knowing the approach and style of each exegete and the sources that he relied on. Then it was compared with the rest of the commentators to find out the aspects of agreement between them and the results obtained from it. Among the factors that call for research is to know the secret of the interest of scholars and commentators, as it is one of the important topics through which we can reach the will of God Almighty, get to know the topic and find out its secrets and the Quranic knowledge it contains; In order to deduce from it the aspects of the agreement between Al-Tusi in the illustration and those who preceded him from the Shiite commentators (in the method and the sources), then presenting and categorizing them within special chapters and comparing them with the explanatory opinions of each of the commentators and coming up with the results.